The effects of a sugar-free amino acid-containing electrolyte beverage on 5-kilometer performance, blood electrolytes, and post-exercise cramping versus a conventional carbohydrate-electrolyte sports beverage and water - Mason C. McIntosh; Bradley A. Ruple; Nicholas J. Kontos; Madison L. Mattingly; Christopher M. Lockwood; Michael D. Roberts (Taylor & Francis Group, 2024)
ABSTRACTObjective The purpose of this study was to examine the acute effects of a multi-ingredient, low calorie dietary supplement (MIDS, XTEND® Healthy Hydration) on 5-kilometer (5-km) time trial performance and blood electrolyte concentrations compared to a carbohydrate-electrolyte beverage (CE, GATORADE® Thirst Quencher) and distilled water (W).Methods During visit 1 (V1), participants (10 men and 10 women, 20-35 years old, BMI ≤ 29 kg/m2, recreationally active) reported to the laboratory whereby the following tests were performed: i) height and weight measurements, ii) body composition analysis, iii) treadmill testing to measure maximal aerobic capacity, and iv) 5-km time trial familiarization. The second visit (V2) was one week after V1 in the morning (0600 - 0900) and participants arrived 12-14 h fasted (no food or drink). The first battery of assessments (V2-T1) included nude body mass, urine specific gravity (USG), a profile of mood states (POMS) questionnaire, and the completion of a visual analogue scale (VAS) questionnaire to quantify cramping. Then heart rate (HR), blood pressure (BP), total body hydration (via bioelectrical impedance spectroscopy [BIS]) were examined. Finally, a measurement of blood markers via finger stick was performed. Participants consumed a randomized beverage (16 fl. oz. of MIDS, 16 fl. oz. of W, or 16 fl. oz. of CE) within 3 min followed by a 45-min rest. Following the rest period, a second battery (V2-T2) was performed whereby participants' USG was assessed and they completed the POMS and VAS questionnaires, and HR, BP, and blood markers were measured. The participants then performed a 5-km treadmill time trial. Immediately following the 5-km time trial, participants completed a third testing battery (V2-T3) that began with blood markers, HR and BP assessments, followed by nude body weight assessment, and the POMS and VAS questionnaires. After 60 min, a fourth battery (V2-T4) was performed that included HR, BP, and blood markers. After sitting quietly for another 60 min a fifth battery assessment was performed (V2-T5) that included participants' USG, POMS and VAS questionnaires, HR, BP, blood markers, and total body hydration. Visits 3 (V3) and 4 (V4) followed the same protocol except a different randomized drink (16 oz. of CE, MIDS, or W) was consumed; all of which were separated by approximately one week.Results No differences occurred between conditions for 5-km time trial completion, indirect calorimetry outcomes during 5-km time trials, USG, or nude mass measurements (p > 0.05 for all relevant statistical tests). However, blood potassium and the sodium/potassium ratio displayed significant interactions (p < 0.05), and post hoc testing indicated these values were better maintained in the MIDS versus other conditions. Post-exercise cramp prevalence was greater in the CE (p < 0.05) and trended higher with W (p = 0.083) compared to the MIDS condition. Post-exercise cramp severity was also elevated with the W and CE beverages (p < 0.05) but not the MIDS (p = 0.211).Conclusions The MIDS did not affect 5-km time trial performance but exhibited favorable effects on blood electrolyte and post-exercise self-reporting cramp outcomes compared to the CE and W drinks.